ChemInform Abstract: Synthesis of Boc‐Protected 4, 5‐Methano‐β‐proline. Issue 44 (4th November 2014) - Tymtsunik, Andriy V.; Ivon, Yevhen M.; Komarov, Igor V.; Grygorenko, Oleksandr O.
Abstract Both cis‐ and trans‐isomers of the title compound are synthesized in 49% total yield.